Meningkatkan Motivasi Belajar melalui Teknik Konseling Cognitive Behavior Therapy - Rina Fatmawati; Fakhruddin Mutakin; Yurike Kinanthy Karamoy (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2018)
Cognitive behavior therapy (CBT) is acounseling approach designeg to solve counsclee problems at this time by way of cognitive restructuring and deviant behavior. Cognitive behavior therapy (CBT) counseling techniques used in indonesia are mind capture, reality testing, cognitive exercices and alternatif search while the motivation to learn is a factor that is unique to arouse or enthusiasm of learning  so have a lot of energy to do learning activities. Learning  motivation is devided in to namely intrinsic and extrinsic motivation. This recearch was conduected in class VIII B MTs ASHRI Jember with the research subject of 30 famale students, but the researcher can only study 10 students who have low learning motivation. Based on analysis show that there is an increase in motivation to learn class VIII B MTs ASHRI Jember after getting counseling service  Cognitive behavior therapy (CBT)with percentage of  71%. Keywords : Cognitive Behavior Therapy (CBT), Motivation Learn